Pharmacogenetic Influences on Individual Responses to Ocular Hypotensive Agents in Glaucoma Patients - Sara Labay-Tejado; Virginia Fortuna; Néstor Ventura-Abreu; Mar Hernaez; Valeria Opazo-Toro; Alba Garcia-Humanes; Mercè Brunet; Elena Milla (Pharmaceutics)
Background/Objectives: To analyze the genotype that predicts the phenotypic characteristics of a cohort of patients with glaucoma and ocular hypertension (OHT) and explore their influence on the response to ocular hypotensive treatment. Methods: This was a prospective study that included 193 eyes of 109 patients with glaucoma or OHT under monotherapy with beta-blockers, prostaglandin, or prostamide analogues (BBs, PGAs, PDs). Eight single-nucleotide polymorphisms were genotyped using real-time PCR assays: prostaglandin-F2α receptor (PTGFR) (rs3766355, rs3753380); beta-2-adrenergic receptor (ADRB2) (rs1042714); and cytochrome P450 2D6 (CYP2D6) (*2 rs16947; *35 rs769258; *4 rs3892097; *9 rs5030656, and *41 rs28371725). The main variables studied were baseline (bIOP), treated (tIOP), and rate of variation in intraocular pressure (vIOP), and mean deviation of the visual field (MD). The metabolizer phenotype and the CYP2D6 copy number variation were also evaluated. Results: In total, 112 eyes were treated with PGAs (58.0%), 59 with BBs (30.6%), and 22 with PDs (11.4%). For PTGFR (rs3753380), statistically significant differences were observed in vIOP in the PGA group (p = 0.032). Differences were also observed for ADRB2 (rs1042714) in MD (p < 0.001) and vIOP (p = 0.017). For CYP2D6, ultrarapid metabolizers exhibited higher tIOP (p = 0.010) and lower vIOP (p = 0.046) compared to the intermediate and poor metabolizers of the BB group. Additionally, systemic treatment metabolized by CYP2D6 showed a significant influence on vIOP (p = 0.019) in this group. Conclusions: These preliminary findings suggest the future potential of pharmacogenetic-based treatments in glaucoma to achieve personalized treatment for each patient, and thus optimal clinical management.